Spline quasi-interpolation numerical methods for integro-differential equations with weakly singular kernels - Saou, Abdelmonaim; Sbibih, Driss; Tahrichi, Mohamed; Barrera, Domingo (Mathematical Modelling and Analysis, 2024)
In this work, we introduce a numerical approach that utilizes spline  quasi-interpolation operators over a bounded interval. This method is designed to provide a numerical solution for a class of Fredholm integro-differential equations with weakly singular kernels. We outline the computational components involved in determining the approximate solution and provide theoretical findings regarding the convergence rate. This convergence rate is analyzed in relation to both the degree of the quasi-interpolant and the grading exponent of the graded grid partition. Finally, we present numerical experiments that validate the theoretical findings.